Gastrointestinal duplication cysts: experience from a tertiary care center in North India and review of literature - Aggarwal, Divya; Vaiphei, Kim (International Surgery Journal, 2020)
Background: Duplication cysts (DC) are uncommon congenital malformations which predominantly present in infants and young children. Owing to their variable clinical presentation, radiology and/or histopathology are often required to clinch the diagnosis. We present a case series of 66 patients, which is the largest series reported so far. Methods: A search of prospectively maintained institutional database was carried out to identify patients who were diagnosed and operated for gastrointestinal DC between January 2013 and August 2018. For all cases, the demographic data, site of DC, details of clinical presentation, associated conditions and histopathology findings were recorded. The slides of all cases were retrieved and re-examined. Results: The age range was 1 day to 47 years, with a slight male predominance (1.3:1). Ileum was the most common site followed by jejunum. Ectopic mucosae noted were gastric, pancreatic, biliary and respiratory. One case showed glial heterotopia. Perforation, gangrene and intussusception were among the co-existing pathologies noted. Conclusions: Duplication cysts are rare congenital malformations. The variability in clinical presentation makes the diagnosis elusive. Timely diagnosis and appropriate management require a high index of suspicion and a holistic diagnostic approach with clinical, radiological and histopathological inputs.